Tomographic study of the structure of cast and pressed trotyl charges - N.P. Satonkina; K.E. Kuper; A.P. Ershov; E.R. Pruuel; A.S. Yunoshev; Ya.L. Lukyanov; D.V. Gusachenko; A.S. Khorungenko; A.A. Kuzminykh (Results in Engineering, 2022)
The sensitivity of condensed explosives depends strongly on the charge structure. Trotyl (TNT) is a typical example of such dependence. The pressed charges are more sensitive than the cast ones, which was confirmed in many studies including critical diameter tests and chemical spike width estimates. Our measurements of the electrical conductivity distributions in the dense TNT support the same conclusion.In this paper, results of tomographic study of the structure of pressed and cast trotyl are presented. The distribution functions of pores larger than 4 μm were obtained using synchrotron X-raying. In cast TNT, voids varying from units to hundred microns were observed, while the pressed charge was found to be substantially more uniform and less porous. The roles of possible mechanisms of hot spots generation are discussed.